Problem-Based Learning as the Basis for the Future Coaches- Instructors’ Professional Training - Павлюк, Євген (Educational Dimension, 2015)
Pavliuk Ye. О. Problem-Based Learning as the Basis for the Future Coaches-Instructors’ Professional Training. The article deals with the classification of the theoretical and methodological foundations of the future coaches-instructors’ professional training with the use of problem tasks. The general content of theoretical and methodological foundations of the future coaches-instructors’ professional training is concretized. An important priority of the future coaches-instructors’ professional training is the professional competence development, especially for senior students.